Work-Related Stress, Burnout, and Well-Being among Nasarawa State University Academic Staff - Stephen S Ojo; Martina A Pojwan (Goodwood Publishing, 2026)
Purpose: Due to the high levels of job-related stress that endanger faculty members' physical and mental health, modern life changes have seriously endangered academic psychological well-being. The main objective of this study was to ascertain the relationship between the psychological well-being of academic staff and work-related stress, burnout, and personality traits. Research Methodology: A cross-sectional survey approach was employed in this study. The study population included male and female academic staff at Nasarawa State University, Keffi, consisting of permanent faculty and lecturers on sabbatical leave. Data for this study were collected using a standardized questionnaire consisting of five sections. Both descriptive and inferential statistics were used for the statistical analysis of the data. Results: The results indicate that there is a significant relationship between academic staff well-being and factors such as personality, work-related stress, and burnout, and that these factors also have a combined effect on their well-being. Conclusions: The study concluded that personality traits, burnout, and work stress all predict psychological well-being among the faculty of Nasarawa State University, Keffi. Limitations: Issues such as burnout and work stress occur over time. Therefore, the design may not rigorously demonstrate the dynamic processes leading to psychological well-being. Contributions: The study will help human resource management of the Nasarawa State University to develop effective workplace intervention strategies that will not only address the variables having a negative impact on the psychological well-being of academic staff but also promote overall well-being for efficient productivity.